Praktik Sewa-Menyewa Kontrakan ditinjau dari Fiqih Muamalah - Anisah, Rezki; Gunawan, Syafri; Simanjuntak, Dahliati (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study discusses the leasing contract carried out by the people of Aek Mual Village, Siabu District, Mandailing Natal Regency in terms of muamalah fiqh. The background of this research is because there are still many people who practice leasing where the contract is not in accordance at the beginning with at the end. The objectives to be achieved in this study are to find out what are the factors that cause people to practice leasing and how to review the muamalah fiqh of leasing that occurs in Aek Mual Village whether it is appropriate according to muamalah fiqh or not. This type of research is field research (field) which is qualitative in nature, namely data collection carried out by direct observation of Aek Mual Village, documentation and interviews with village people who practice leasing rented houses in Aek Mual Village. After obtaining complete data, it is then analyzed using deductive reasoning analysis methods, namely explaining the views of the lease first, then analyzing the applicable regulations, namely Fiqh Muamalah. The results of the study show that the factors that influence the community to lease are the first, population movement, movement of residents from the city to the village or from one village to another, this is what causes someone to rent to get a place to live in Aek Mual Village. Two people who have just married, most people who have just married will rent this out on the basis of not having enough money to build a house. The leasing practice transactions carried out by the people of Aek Mual Village are not fully in accordance with the Fiqh Muamalah agreements that are not suitable at the beginning and end (contract). In Fiqh Muamalah the contract (agreement) at the beginning must be in accordance with the agreement at the end as agreed by both parties.